Detection of Early Renal Damage using Serum Cystatin-C in Transfusion Dependent Thalassemia Syndrome Patients - Bashir, Sobia; Farooq, Nazish; Masood, Muhammad Tariq; Farid, Nayab; Khan, Aamir; Nowshad, Mahwish (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Background: Transfusion-dependent thalassemia (TDT) patients suffer from several life-threatening complications. These mainly stem from iron overload, a common adverse effect of regular transfusions. Studies discerning renal complications are, however, scarce. Objective: This study investigatesthe frequency of early renal damage among TDT patients using serum cystatin-C. The relationship between serum cystatin-Cand serum ferritin levels is also elucidated. Design: Cross-sectional study Place & duration of study: Khyber Medical University, May 2019 to January 2020 Methodology:Known TDT patients, 3 to 16 years of age, were enrolled in the study.Biochemical tests were conducted on the blood and urine samples of the patients. Data was entered and analyzed for statistical significance. Results:In pediatric TDT patients, serum cystatin-C was significantly higher, while serum creatinine and estimated glomerular filtration rate (eGFR)were within the normal range when compared to controls. A positive correlation was identified between serum cystatin-Cand serum ferritin. Similarly, Serum cystatin-Cwas found to have a positive correlation with pretransfusion hemoglobin.The interval of transfusion was, however, inversely associated with serum cystatin-C levels. Conclusion:Asymptomatic renal dysfunction is found in TDT patients. Thismay be attributed to iron overload. Keywords:Transfusion dependent thalassemia, Thalassemia Major, Renal functions, serum Creatinine, Serum cystatin-C, Glomerular filtration rate